"Musik am Rande" - Reittererová, Vlasta (Muzikološki zbornik, 2011)
Alois Hába is usually characterised as one of the leading protagonists of the Central European interwar avant-garde. He is primarily known as a tireless propagator of microtonal and athematic music, for which his own term was 'liberated music'.
Keywords: Czech music; češka glasba; Hába, Alois, 1893-1973; microtone music; mikrotonalna glasba